Systemic View to Understanding Design Change Causation and Exploitation of Communications and Knowledge. Issue 3 (June 2019) - Yap, Jeffrey Boon Hui; Skitmore, Martin; Gray, Jason; Shavarebi, Kamran
Frequent changes pervasively undermine project schedule performance. Despite voluminous research into project delays, however, the persistence of the problem demands that a systemic approach be adopted to investigate design change causation and to explore the efficacy of communications and knowledge as strategic project controls. Drawing on a hybrid research design, the critical variables are identified and mapped onto causal loop diagrams to enable practical holism. The findings indicate that effective project communications engenders collaborative team dynamics and collective learning, whereas project learning contributes to knowledge reuse and the improved expert judgment needed for transforming design change management and schedule control.